Using Fast-Time Simulations for Designing and Operating Airport Terminals as Nodes of Intermodaltransport - Benedikt Badanik; Milan Stefanik; Martin Matas (Communications - Scientific letters of the University of Zilina, 2011)
Ever growing traffic in air transport with associated capacity constraints brings problems to air passenger flows at airports. There is strong link between quality of airport ground access system and airport terminal operations. However, this aspect remains underestimated in the development plans of many airports all over the world, which results in underutilization of both planed and existing infrastructure. In efforts for improvement, the higher level of synchronization and coordination between air and ground transport needs to be achieved. For this purpose, a computer model enabling to simulate passenger flows within airport’s catchment area has been developed by the Air Transport Department, University of Zilina. Thanks to this simulation model, it is possible to perform comprehensive operational, economic and environmental assessment of the innovative airport ground access concepts and thus facilitate designing and operating airports as nodes of intermodal transport.